Cutaneous legionellosis: case report and review of the medical literature. Issue 2 (17th March 2014) - Padrnos, L.J.; Blair, J.E.; Kusne, S.; DiCaudo, D.J.; Mikhael, J.R.
Abstract Discrete nodules developed on the leg of a 27‐year‐old immunosuppressed woman after an allogeneic stem cell transplant. Biopsy and culture grew Legionella pneumophila serogroup 8. On day 7 of azithromycin treatment, respiratory distress and abnormal liver transaminases developed, and the patient died on day 14. Review of the medical literature identified 19 reports of Legionella species‐associated skin or soft tissue infections (total of 20 patients, 13 with confirmed infection). Manifestations of the 13 confirmed cases included erythematous macular rash (n = 7), erythema after thoracentesis (n = 1), abscess formation (n = 4), respiratory symptoms (n = 6), and abnormal chest radiographs (n = 8). Six required surgical exploration and débridement, and 7 were immunocompromised. Rash and respiratory infection improved with antibiotics in 10, but 3 died. Immunosuppression may predispose transplant recipients to Legionella infections. Diagnostic biopsies may facilitate appropriate treatment.